Estimating the Decadal Predictability of a Coupled AOGCM. - Pohlmann, H.; Botzet, M.; Latif, Mojib; Roesch, A.; Wild, M.; Tschuck, P. (Journal of Climate, 2004)
On seasonal time scales, ENSO prediction has become feasible in an operational framework in recent years. On decadal to multidecadal time scales, the variability of the oceanic circulation is assumed to provide a potential for climate prediction. To investigate the decadal predictability of the coupled atmosphere–ocean general circulation model (AOGCM) European Centre-Hamburg model version 5/Max Planck Institute Ocean Model (ECHAM5/MPI-OM), a 500-yr-long control integration and “perfect model” predictability experiments are analyzed. The results show that the sea surface temperatures (SSTs) of the North Atlantic, Nordic Seas, and Southern Ocean exhibit predictability on multidecadal time scales. Over the ocean, the predictability of surface air temperature (SAT) is very similar to that of SST. Over land, there is little evidence of decadal predictability of SAT except for some small maritime-influenced regions of Europe. The AOGCM produces predictable signals in lower-tropospheric temperature and precipitation over the North Atlantic, but not in sea level pressure.